2006
DOI: 10.1007/s10047-005-0325-9
|View full text |Cite
|
Sign up to set email alerts
|

Femoral arteriovenous fistula: a complication of temporary hemodialysis catheter placement

Abstract: The femoral vein is increasingly being used as a temporary route for dual-lumen hemodialysis catheter placement because it is thought to be safer than the internal jugular or subclavian vein sites. However, several factors preclude the wider use of indwelling femoral catheters for hemodialysis, including interference with ambulation and concern over bleeding, infection, and deep thrombosis. Herein we describe a case of right superficial femoral arteriovenous fistula as a complication of the insertion of a dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…1 Moreover, the use of a fine-gauge needle to locate the vein before introduction of the guide wire using the Seldinger needle is suggested as well. 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Moreover, the use of a fine-gauge needle to locate the vein before introduction of the guide wire using the Seldinger needle is suggested as well. 12 …”
Section: Discussionmentioning
confidence: 99%
“…AVF as a complication of dual-lumen HD catheter insertion has been described in the medical literature. Kuramochi et al 12 described a case of right superficial femoral AVF with a symptom of arterial bleeding. Chiba et al 13 reported a case of an AVF associated with calf pain 2 months after the removal of the catheter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This site is often favored by many because it carries no risk for pneumothorax, falsely obviating the need for image guidance. 3 This likely accounts for its frequent use in placing temporary dialysis catheters. However, as is often the case, a lack of imaging guidance and anatomical understanding of the relationship between the femoral artery and its bifurcation vessels relative to the femoral vein may lead to a low access within the upper thigh, resulting in traumatic injury of the superficial femoral artery as in this case.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by El Minshawy et al, common complications are infections (40%), thrombosis (7.5%), bleeding from a punctured femoral artery (5%), and groin hematoma (0.5%) (2). Other rare complications that have been described in case reports include pulmonary thromboembolism, femoral arteriovenous fistula, retroperitoneal hematoma, and psoas muscle abscess (3)(4)(5)(6). In this report, we describe the case of femoral vein perforation with prevesical hematoma after inserting a temporary hemodialysis catheter.…”
Section: Introductionmentioning
confidence: 96%